Pengalaman Mahasiswa Keperawatan dalam Pemenuhan Kebutuhan Dasar Manusia Rekreasi - Natalia Ratna Yulianti; Dea Rachel Noela; Eva Dwi Fransiska; Lumintan Efriyanti; Vera Dwi Kristyana; Yuventia Ratna Pratiwi (LPPM STIKES KENDAL, 2020)
Recreation is one of the basic human needs, however people are not often able to meet this need because they are too busy with work or having too many tasks to do. These people include nursing students, who are well known to have a lot of tasks and examinations. Studies on recreation needs among nursing students had been conducted, yet little is known of studies which explore topics with qualitative methods. This study is aimed to explore nursing students’ experience on fulfillment of recreation needs while doing many tasks and examination. Qualitative method with phenomenology design was chosen in order to attain the goal. Samples were determined using purposive sampling technique with inclusion criteria: students who experience that their tasks and examination were too many. Four nursing students were involved as participants. Data were gathered by employing in-depth interview in a focus group discussion (FGD). Subsequently the data were analyzed using Colaizzi method. There were three themes that emerged and are as follows “We have our own way to refresh our mind”, “Yes, our basic human need: recreation is fully met”, and “Sometimes obstacles are inevitable” which then were formulated to an essential structure “Be creative to create our own recreation although sometimes there were obstacles.” This study encourages nursing educators to ensure that the recreation needs of every nursing student is fulfilled.